(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The phenomenon of realization of legal responsibility of the state, which has gone beyond the framework of generally accepted public-law relations, is considered. The situation arising in this case requires the restoration of the rights of society and the individual in a country where power is usurped by a criminal regime, as well as international law violated by a criminal state. The legal consequences for the delinquent State in case of its disregard for the norms of international and national law are analyzed.